Susceptibilidade de isolados brasileiros de Brucella abortus a agentes antimicrobianos utilizados no tratamento da brucelose humana - Rebeca Barbosa Pauletti (2010)
The goal of this update of brucellosis as a zoonotic disease is to address the human brucellosis and its epidemiological situation in Brazil and in the world, their sources of infection and risk groups, clinical symptoms, treatment and characteristics of the antimicrobials used to treat disease in humans. It discusses the role of Brucella spp. as an agent of bioterrorism.